Capitalismo consciente e seus princípios: percepções dos gestores em empresas no interior do Ceará - Silva, Rodrigo Farias da (2023)
Capitalism has created significant wealth for the population in general, providing a considerable level of production freedom, fostering a culture of knowledge pursuit and professionalization. However, when this economic system is observed more closely, it becomes evident that it presents structural problems in its conception. Conscious Capitalism emerges with the intention of redesigning these problematic pillars in traditional capitalism. The term Conscious Capitalism was introduced into the business and academic world in 2008 by its founders, John Mackey and Raj Sisodia. The concept is based on the principles of a higher purpose, stakeholder integration, conscious leadership, and conscious culture, understanding that capitalism can be a force for both the economy and social well-being, as well as for the environment. It is understood that conscious cultures are based on conscious values, with values indicating the behaviors manifested in the organization. These behaviors, in turn, sustain the organizational culture, which is influenced by the behaviors of the managers. This study, which combined quantitative and qualitative approaches, aimed to assess the willingness of 40 managers from companies located in the interior of Ceará to adopt Conscious Capitalism practices. Using the Seven Levels of Consciousness Evolutionary Method developed by Richard Barrett, the research aimed to determine the levels of consciousness of these leaders based on their values to identify their predisposition to implementing conscious practices in their organizations. The results indicated that the majority of the participating managers, according to the method used, showed lower levels of consciousness and, consequently, a lower affinity for practices related to Conscious Capitalism in their organizations. Although a hypothetical analysis based on the two questionnaires suggested that managers in Group 2 were more aligned with the principles of Conscious Capitalism, upon examining their speeches, it was clear that most of them were distant from this concept. This points to a significant disparity between the questionnaire responses and what was expressed in the interviews.